2013
DOI: 10.1080/09518398.2013.816887
|View full text |Cite
|
Sign up to set email alerts
|

Seeing red? The agency of computer software in the production and management of students’ school absences

Abstract: Linnea Bodén is a Ph.D. student of Educational practice at the Department of Social and Welfare Studies, Linköping University. Her research focuses on school absenteeism and truancy and draws on a feminist relational materialist and posthumanist perspective, with a special interest in technical tools for the registration and control of absence. 2Seeing red? The agency of computer software in the production and management of students' school absences An increasing number of Swedish municipalities use digital so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…As I have shown elsewhere (Bodén, 2013b), materialities like computer software are part of producing school absence. In this article, however, the focus is on the material-discursive intraactions taking place in the process of registration and how to account for this-not only in the analysis but also methodologically.…”
Section: Introduction: Exploring the Materiality Of Qualitative Methodologiesmentioning
confidence: 94%
See 1 more Smart Citation
“…As I have shown elsewhere (Bodén, 2013b), materialities like computer software are part of producing school absence. In this article, however, the focus is on the material-discursive intraactions taking place in the process of registration and how to account for this-not only in the analysis but also methodologically.…”
Section: Introduction: Exploring the Materiality Of Qualitative Methodologiesmentioning
confidence: 94%
“…Each field on the screen represented 1 day and each used a specific color to indicate whether the student had been present or absent that day. A green field showed that the student had been present the whole day, a yellow field that the student was absent but that the absence was valid and that the parents had reported it beforehand, and a red field that the student had been absent and the absence was invalid (see also Bodén, 2013b). When opening the page, Malin said, This is someone who is absent so much that I will call the parents today, I think.…”
Section: Carlmentioning
confidence: 99%
“…Theoretically, these posthumanities studies are inspired by Gilles Deleuze and Felix Guattari (Pedersen 2013;Mazzei 2013;Bodén 2013;Johansson 2014) as well as Karen Barad (Rosiek 2013;Hultman and Lenz Taguchi 2010) and approaches from science and technology studies in general and actor-network theory in particular (Fenwick and Landri 2012;Ceulemans, Simons, and Struyf 2012). Methodologically, these studies use ethnographic fieldwork (Pedersen 2013;Bodén 2013) as well as interviews (Mazzei 2013;Hultman and Lenz Taguchi 2010). A common denominator is the emphasis on decentering the individual human subject and attending to the agency of the material and the nonhuman world.…”
Section: Research Context Ii: Posthumanities Educationmentioning
confidence: 99%
“…The text messages could thus be described as engaged in affective flows as they stir things up, become 'stirrers', and productive of both emotions and material practices related to school absenteeism. And how this is enacted and what will be produced is always connected to the various entanglements within the assemblage (Bodén 2013).…”
Section: Going With the Affective Flows Of Text Messages -A Theoreticmentioning
confidence: 99%
“…The messages are often digitally automated, sent directly from software like Dexter, into which teachers before, during, or after each lesson digitally register the students' absences and presences. These kinds of software and the messages produced have been described as problem-solving tools to make the management of absences more efficient (Bodén 2013;, see also Bhalla et al 2013;Gavade et al 2015;Isomursu et al 2011;Lodha et al 2015;More and Nayak 2013).…”
mentioning
confidence: 99%